MYH9-dependent polarization of ATG9B promotes colorectal cancer metastasis by accelerating focal adhesion assembly - Zhong, Yan; Long, Ting; Gu, Chuan-Sha; Tang, Jing-Yi; Gao, Ling-Fang; Zhu, Jia-Xian; Hu, Zhi-Yan; Wang, Xia; Ma, Yi-Dan; Ding, Yan-Qing; Li, Zu-Guo; Wang, Xiao-Yan (Cell death and differentiation, 2021)
Tumour metastasis is a major reason accounting for the poor prognosis of colorectal cancer (CRC), and the discovery of targets in the primary tumours that can predict the risk of CRC metastasis is now urgently needed. In this study, we identified autophagy-related protein 9B (ATG9B) as a key potential target gene for CRC metastasis. High expression of ATG9B in tumour significantly increased the risk of metastasis and poor prognosis of CRC. Mechanistically, we further find that ATG9B promoted CRC invasion mainly through autophagy-independent manner. MYH9 is the pivotal interacting protein for ATG9B functioning, which directly binds to cytoplasmic peptide segments aa368–411 of ATG9B by its head domain. Furthermore, the combination of ATG9B and MYH9 enhance the stability of each other by decreasing their binding to E3 ubiquitin ligase STUB1, therefore preventing them from ubiquitin-mediated degradation, which further amplified the effect of ATG9B and MYH9 in CRC cells. During CRC cell invasion, ATG9B is transported to the cell edge with the assistance of MYH9 and accelerates focal adhesion (FA) assembly through mediating the interaction of endocytosed integrin β1 and Talin-1, which facilitated to integrin β1 activation. Clinically, upregulated expression of ATG9B in human CRC tissue is always accompanied with highly elevated expression of MYH9 and associated with advanced CRC stage and poor prognosis. Taken together, this study highlighted the important role of ATG9B in CRC metastasis by promoting focal adhesion assembly, and ATG9B together with MYH9 can provide a pair of potential therapeutic targets for preventing CRC progression.